Role of oxidative mechanisms in the pathogenesis of age-related macular degeneration - Janik-Papis, Katarzyna; Ulińska, Magdalena; Krzyżanowska, Anna; Stoczyńska, Ewelina; Borucka, Anna; Woźniak, Katarzyna; Zaraś, Małgorzata; Szaflik, Jacek P.; Błasiak, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Oxidative stress is a major factor in the pathogenesis of age-related macular degeneration (AMD). Retinal pigment epithelial (RPE) cells are prone to reactive oxygen species (ROS) arising during the stress due to intense oxygen metabolism and a high oxygen pressure. Additionally, the cells can be exposed to ROS as a consequence of accumulation of iron ions in these cells, sunlight exposure and tobacco smoke. There are several defense systems against RTF in the cell, including antioxidant enzymes, low-molecular weight antioxidants and DNA repair pathways. RPE cells display phagocytic activity towards outer segments of photoreceptors and this activity can be associated with additional oxidative stress since the segments are rich in long chain, polyunsaturated fatty acids (PUFA). The oxidation of PUFA leads to the production of additional ROS. Moreover, oxidized PUFA are not correctly cleaved in the lysosomes of RPE and are accumulated in the form of lipofuscin, which is deposited in Bruch’s membrane in the form of drusen and in this way it stimulates immune responses, including phagocytosis, associated with the recruiting of macrophages and dendritic cells. In this time, RPE cells are exposed to ROS, produced in oxygen burst associated with phagocytosis. Further studies, both clinical/epidemiological and in vitro, are needed to better understand relationship between AMD and oxidative stress.